2017
DOI: 10.1038/s41598-017-10639-w
|View full text |Cite
|
Sign up to set email alerts
|

Chronic interfacing with the autonomic nervous system using carbon nanotube (CNT) yarn electrodes

Abstract: The ability to reliably and safely communicate chronically with small diameter (100–300 µm) autonomic nerves could have a significant impact in fundamental biomedical research and clinical applications. However, this ability has remained elusive with existing neural interface technologies. Here we show a new chronic nerve interface using highly flexible materials with axon-like dimensions. The interface was implemented with carbon nanotube (CNT) yarn electrodes to chronically record neural activity from two se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
97
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(100 citation statements)
references
References 53 publications
(47 reference statements)
3
97
0
Order By: Relevance
“…) of the vagus nerve. Preclinical studies for chronic vagus nerve electrodes have been successfully conducted in large animal models (Zhang et al 2009;Ardell et al 2017;Hamann et al 2013;Metcalfe et al 2018;Valdés-Cruz et al 2002) and in rats (Somann et al 2017;McCallum et al 2017;Grimonprez et al 2015;Li et al 2004;Khodaparast et al 2016). Thus far, no studies for chronic mouse vagus nerve interfacing have been reported.…”
mentioning
confidence: 99%
“…) of the vagus nerve. Preclinical studies for chronic vagus nerve electrodes have been successfully conducted in large animal models (Zhang et al 2009;Ardell et al 2017;Hamann et al 2013;Metcalfe et al 2018;Valdés-Cruz et al 2002) and in rats (Somann et al 2017;McCallum et al 2017;Grimonprez et al 2015;Li et al 2004;Khodaparast et al 2016). Thus far, no studies for chronic mouse vagus nerve interfacing have been reported.…”
mentioning
confidence: 99%
“…Unveiling spike patterns of the vagus nerve is indispensable to further understand the communication between the brain and visceral organs such as the heart (Hayakawa et al, 2011), digestive organs (Campos et al, 2012;Czaja et al, 2006), and the lung (Han et al, 2018;Weijs et al, 2015). In previous studies, recordings of VN spikes have been performed in anesthetized rodent animals (Caravaca et al, 2017;Harreby et al, 2011;McCallum et al, 2017;Silverman et al, 2018). Here, we developed a new method to record electrical spikes from the cervical VN using a cuff-shaped electrode in a freely moving animal, which was integrated with our existing method to record bioelectrical signals from multiple organs, including the brain, cardiac system, breathing system, and skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
“…While early studies performed vagus nerve recordings from anesthetized animals (Caravaca et al., ; Harreby, Sevcencu, & Struijk, ; McCallum et al., ; Silverman et al., ), recordings from freely moving animals have been limited due to technical difficulties. To address this issue, we developed a novel recording method that can monitor vagus nerve (VN) spikes with a cuff‐shaped electrode from a freely moving rat.…”
Section: Introductionmentioning
confidence: 99%
“…After about 20 years of intensive study, the mechanical performance of CNT fibers have approached the commercial carbon fibers very quickly (Figure e). The improved strength and modulus have ensured various stable applications such as supercapacitor and battery, implantable electrode, multifunctional fabrics, antenna, and so on. However, it is still difficult to realize a continuous CNT fiber with a tensile strength competitive with carbon fiber.…”
Section: Structure and Fundamental Propertiesmentioning
confidence: 99%